Research on the development height of water-conducting fracture zone in overburden rock based on transient electromagnetic method in hole - Qinghua LIANG; Xiangjun DING; Guangliang LIU; Zhicheng LIU; Chunyuan WANG; Huan ZHANG (Meikuang Anquan)
Transient electromagnetic method has shown great effectiveness in detecting water channels. However, conventional methods for detecting the development of water-conducting fracture zones are not suitable due to environmental influences. In this study, the borehole transient electromagnetic method was used to investigate the development height of water-conducting fracture zones in the overlying strata underground. The propagation characteristics and response features of the borehole transient electromagnetic method were studied using COMSOL software. Combined with borehole transient electromagnetic testing, the feasibility of detecting water-conducting fracture zones using the borehole transient electromagnetic method was investigated. The research results showed that the borehole transient electromagnetic method can effectively complete the task of detecting anomalous bodies. The signal-to-noise ratio can be improved by adjusting the position of the transmitter-receiver devices. The radial diffusion mode of the borehole transient electromagnetic method is basically the same as the theory of mine transient electromagnetic. However, simulations revealed that the response field of low-resistivity zones is greatly affected by high-resistivity zones, resulting in rapid attenuation of adjacent low-resistivity zones near the 60 m interface and the appearance of “peak points” in the response curve of the low-resistivity zones. This indicates that the apparent resistivity of the low-resistivity zones near the 60 m interface is greater than the theoretical value of the low-resistivity zones due to the influence of high-resistivity rock masses. Through underground experiments, it was concluded that the borehole transient electromagnetic method can effectively detect the significant abnormal development of water-conducting fracture zones in mined coal seams, which are connected in large patches. In contrast, the low-resistivity anomalies in unmined coal seams using the transient electromagnetic method are not obvious, and large-scale connections have not been formed. This suggests that observing the development of water-conducting fracture zones through the borehole transient electromagnetic system is highly feasible.